Advanced concepts for intelligent vision systems : 19th International Conference, ACIVS 2018, Poitiers, France, September 24-27, 2018, Proceedings /: 19th International Conference, ACIVS 2018, Poitiers, France, September 24-27, 2018, Proceedings. (2018) - Unknown
No abstract available